In(OTf)3/acid co-catalyzed hydration of 1-haloalkynes to α-halomethyl ketones. Issue 27 (7th July 2016) - Zeng, Ming; Huang, Rui-Xue; Li, Wen-Yi; Liu, Xiao-Wen; He, Fu-Ling; Zhang, Yi-Yuan; Xiao, Fang
Abstract: A novel and efficient In(OTf)3 and HOAc cooperatively catalyzed hydration of 1-haloalkynes is described. This method provides ready access to α-chloromethyl ketones, α-bromomethyl ketones and α-iodomethyl ketones in moderate to high yields from simple, inexpensive starting materials. A broad substrate scope is achieved, and the reaction is compatible with various functional groups, including alkoxy, trifluoromethyl, halide, hydroxyl, cyclohexyl, and heterocyclic groups. Graphical abstract: